Answer:
x = (c+a)/2
y = (c-a)/2
Explanation:
Add the two equations and you get ...
(x +y) +(x -y) = (c) +(a)
2x = c+a
x = (c+a)/2
--
Subtract the second equation from the first and you get ...
(x +y) -(x -y) = (c) -(a)
2y = c-a
y = (c-a)/2
_____
Comment on this problem
This is what I call a "sum and difference" problem. The solution shown here is (obviously) the generic solution to such a problem. Remembering this can get you quickly to the answer any time you're given the sum of two unknowns and their difference.